Pranalisis Penerapan Truck Loading System (TLS) Terhadap Pengoptimalan Efektivitas dan Efisiensi Coal Loading Pada ROM Stockpile PT. BCD - Ruben Laurensus Baringbing; Maryono (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This study aims to determine the advantages of the implementation of TLS since 2021 in increasing effectiveness and efficiency in terms of coal laoding. The research method used is a qualitative approach with a case study design that focuses on TLS evaluation at PT BCD through field observation, interviews, and secondary data analysis. The results of the study show that the application of Truck Loading System (TLS) at PT BCD is proven to have great potential in increasing the effectiveness and efficiency of coal loading in ROM with productivity achieved according to plan, increasing loading speed, minimizing fuel use, and increasing load accuracy through monitoring technology and the use of scrappers. To optimize the effectiveness and efficiency of TLS systems, good maintenance can reduce the risk of downtime, which can have a significant impact on productivity. In addition, corrective maintenance must also be carried out efficiently to ensure that operational disruptions can be overcome quickly. In other words, the effectiveness and efficiency of TLS is from maintaining its equipment and maximizing facilities for employees and maximizing TLS so that it can be used for loading on all types of means of transportation. Some of the recommendations given are to carry out routine maintenance of TLS, replace TLS crew facilities to make them more ergonomic